Nations of Writers - Réda Bensmaïa (Studies in 20th & 21st Century Literature, 1999)
In a speech given at the first Algerian National Colloquium on Culture, M. Lacheraf, a Maghrebian historian and former Minister of National Education, addressed the question of minimal requirements for the development of a Maghrebian culture, asking the following question: "At what level already or yet to be reached, does a national culture cease to be mere entertainment and become as basic as the bread one eats and the air one breathes?"...
Keywords: Algerian National Colloquium; culture; Culture; M. Lacheraf; Maghrebian historian; Minister of National Education; Maghrebian culture; national culture